2016
DOI: 10.1038/srep36000
|View full text |Cite
|
Sign up to set email alerts
|

Novel pH sensing semiconductor for point-of-care detection of HIV-1 viremia

Abstract: The timely detection of viremia in HIV-infected patients receiving antiviral treatment is key to ensuring effective therapy and preventing the emergence of drug resistance. In high HIV burden settings, the cost and complexity of diagnostics limit their availability. We have developed a novel complementary metal-oxide semiconductor (CMOS) chip based, pH-mediated, point-of-care HIV-1 viral load monitoring assay that simultaneously amplifies and detects HIV-1 RNA. A novel low-buffer HIV-1 pH-LAMP (loop-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Elsewhere, emerging alternative NAAT solutions focus on the energy efficiency of isothermal amplification technologies 64 as well as the agnostic, de novo analytical power of memory stick-sized sequencing systems. 65 , 66 Whilst many of these have been successfully evaluated in resource-limited settings, 64 , 65 these solutions still require extensive and costly laboratory infrastructure for sample pre-processing 64 66 even onto genome extraction, 65 , 66 are non-quantitative, 64 closed access, 64 , 66 or require high bandwidth data transfer/computational power access 65 , 66 to realize their potential.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, emerging alternative NAAT solutions focus on the energy efficiency of isothermal amplification technologies 64 as well as the agnostic, de novo analytical power of memory stick-sized sequencing systems. 65 , 66 Whilst many of these have been successfully evaluated in resource-limited settings, 64 , 65 these solutions still require extensive and costly laboratory infrastructure for sample pre-processing 64 66 even onto genome extraction, 65 , 66 are non-quantitative, 64 closed access, 64 , 66 or require high bandwidth data transfer/computational power access 65 , 66 to realize their potential.…”
Section: Discussionmentioning
confidence: 99%
“…Ion-sensitive field-effect transistors (ISFETs) are emerging potentiometric sensors for nucleic-acid based applications. Implementation in unmodified complementary metal-oxide-semiconductor (CMOS) technology provides ISFETs with inherent sensitivity to pH, which has enabled DNA detection by employing an adapted version of LAMP, called pH-LAMP, that allows changes in pH to occur during nucleic acid amplification [20][21][22] . Recently, in Malpartida-Cardenas et al 23 , it was shown that this approach holds significant potential for the development of a cheap, portable and quantitative diagnostic tool.…”
mentioning
confidence: 99%
“…[18][19][20][21] Gurrala et al used RT-LAMP to amplify HIV-1 RNA and produce a pH change that can be measured with their device. 22 The lack of reagent storage and integrated sample preparation, however, decreases the translatability of this and other RT-LAMP devices.…”
Section: Introductionmentioning
confidence: 99%